If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -5 = 9 + -6x Reorder the terms: -5 + 10x = 9 + -6x Solving -5 + 10x = 9 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -5 + 10x + 6x = 9 + -6x + 6x Combine like terms: 10x + 6x = 16x -5 + 16x = 9 + -6x + 6x Combine like terms: -6x + 6x = 0 -5 + 16x = 9 + 0 -5 + 16x = 9 Add '5' to each side of the equation. -5 + 5 + 16x = 9 + 5 Combine like terms: -5 + 5 = 0 0 + 16x = 9 + 5 16x = 9 + 5 Combine like terms: 9 + 5 = 14 16x = 14 Divide each side by '16'. x = 0.875 Simplifying x = 0.875
| C=2*3.14*3 | | 130+4x=234-2.5x | | a-3b=43 | | y-4(2-y)+3y=3(y-4) | | X(a-4b)=5m(x-c) | | 9.375=X/4 | | 3p=4/5 | | (-4x^6d^3)(6x^3d)= | | 6.5x=104 | | n=(n+8)/3 | | 13(x+2)(x+2)-5=22 | | x*2/3+6=-3 | | 16(z-1)(z-1)-29=-28 | | lx+2l=3x | | x*1=1 | | 9(z+1)(z+1)+12=16 | | x=-5+3y | | 7x-4=-46 | | (y+3)(y+3)=4 | | p+26=22 | | -2/3a=6 | | 12(x-11)(x-11)+12=30 | | a^2+b^2-1=0 | | 9d+(8+5.5)=24 | | 81n+33=42 | | p-13=-5 | | 4(9-y)xy+4y=36 | | 9d+(8+6)=24 | | 25(z+2)(z+2)-35=-36 | | h=9 | | 4(9-y)+4y=36 | | 0=(x^2-31x-32)/40 |